Reservoir Characterization Using Amplitude Versus Offset (AVO) Analysis of Lakota Formation, Teapot Dome Field, Wyoming, USA - Samudera, Nadia; Herawati, Ida (Physics Study Programme, Faculty of Science and Technology UIN Syarif Hidayatullah Jakarta, 2024)
Lakota Formation is one of the prolific formations at Teapot Dome Field. The objective of this study is to analyze hydrocarbon potential of Lakota Formation using Amplitude Versus Offset (AVO) analysis. AVO analysis is performed to determine AVO class, intercept (A) and gradient (B) values of Lakota reservoir. This study uses pre-stack 3D gather data and three wells, 17-WX-21, 48-X-28 and 41-2-X-3. The Lakota formation is known to be an oil-bearing sandstone reservoir which supported by log interpretation. Analysis of AVO modelling using well data by crossplotting reflectivity (R) with sin2 θ, shows that the Lakota Formation is in Class IIP for wells 17-WX-21 and 41-2-X-3 and Class II for well 48-X-28. An estimation of AVO intercept and gradient based on the seismic data show that the Lakota Formation is class II AVO response. A-B plane shows that the pay zones of Lakota formation are fall within hydrocarbon zone, but very close to background trend (wet sands/shale). AVO attributes; A*B and scaled Poisson Ratio at well location showing difficulty in differentiate the presence of oil and brine. Therefore, it can be concluded that AVO attributes can not distinguish between water and oil zone in Lakota Formation, and therefore we can not determine distribution of oil in the Lakota reservoir.